Ketika Kerusakan Lingkungan Menjadi Komoditi Globalisasi (Studi Kritis Pembangunan Berkelanjutan Sektor Kehutanan di Indonesia) - Kristanti, Dwi (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2014)
This paper aims to describe Sustainable Forest Management as alternative development to break forestdamaging which is caused by unenvironmental development, i.e.modernization. In fact, it is found thatin the activity of Sustainable Forest Management, the role of global actors still is dominated, mainly tocope iilegal logging and forest conservation and rehabilitation project, example in Industry PlantsForest. Besides that, their mission oriented to economic growth which sustaining of forest would beaffected to sustain global trading of forest commercial commodity. On this paper, the writer argument isthat environmental destroying has become globalization commodity. Therefore, Indonesia should beincrease its roles with engaged communities participation. These purpose to create be autonomous andreduce dependences to global actors or International institution